Developing a Valid and Reliable Tool to Measure Patience in Avoiding Sinful Behaviour (Iffah) Among Indonesian Muslim Youth - Ramadhani, Rifqi; Malay, M. Nursalim; Isnaini, Nurul (Psikis : Jurnal Psikologi Islami, 2025)
Moral degration among Indonesian teenagers shows a worrying trend, with increasing violations of socio-religious norms. Although there have been several measuring instruments to measure patience, none have precisely asessed patience in the context of avoiding sin. This research employed a psychometric approach related to patience in sin (iffah) based on Al-Jauziyyah (1998). This study involved 476 respondents (316 females, 160 males) ages 18-21 years. Instrument development went through stages of literature review, expert judgment (two psychology experts and three Islamic scholars), and psychometric testing. Analysis using Exploratory Factor Analysis (EFA) in JAMOVI 2.3 software with ‘minimum residual’ extraction method and ‘oblimin’ rotation produced a valid and reliable two-factor structure, explaining 45.1% of total variance. Analysis results showed a KMO value of 0.943 and significant Bartlett’s Test (p<0.001), with good model fit (RMSEA = 0.0589; TLI = 0.937). From 45 initial items, 18 items were retained, after purification based on psychometric criteria. This scale offers a valid and reliable measuring instrument to evaluate interventions in developing patience among Indonesian Muslim adolescents in facing moral challenges in the digital era